Mid þearfum wædum. Rappresentare la povertà nella poesia anglosassone - Carla Cucina (Filologia Germanica)
Poverty was certainly part of the Anglo-Saxon experience. In the literary corpus, there are several hints which prove that it was  considered one of those very hard physical and psychological tests – such as extreme cold, pain, illness, old age, solitude, exile – men happen to face in their lifetime. Christian perspective intervenes in turning the moral perception of wealth vs. poverty upside down, with material values superseded by the spiritual acceptance of the model of Christ, who chose to stand on the beggar’s side. Through the doctrine of charity, the idea that the rich man has to give to the poor a portion of his possessions – since ultimately these are on loan from God – makes its way into society, so that a new and basically penitential carrying out of the traditional gifstol power system emerges. The purpose of this essay is to select from the corpus of Old English poetry significant examples both of paupertas cum Petro (i.e. poverty voluntarily chosen as a devotional form of life) and of paupertas cum Lazaro (i.e. indigence suffered as a permanent or occasional condition), as well as to find poetic evidence for the Christian idea that, since earthly wealth is granted by God, it has to be generously distributed by the wealthy men in the form of alms, which become the safest way for them to save their own soul. By reading the poetic corpus and also by taking into account some significant interactions of thought with and verbal echoes of both the homiletic tradition and the relevant Latin sources, the present analysis demonstrates that a wide range of types or aspects of poverty are represented in Old English poetry. Moreover, it shows that the material and psychological effects of poverty – even if the Anglo-Saxons certainly had no social conscience in the modern sense – were especially moving for authors, particularly when they could draw on the so-called “elegiac” set of topoi, such as precariousness, exile, loss, separation, solitude.